French Loanwords in Canadian English: A Usage-Based Approach - Julie Rouaud (Anglophonia)
This paper focuses on the semantic evolution of French loanwords adopted into Canadian English from the seventeenth century onwards. Our lexical database of Canadianisms of French origin, extracted from historical dictionaries and works on contemporary Quebec Gallicisms, was verified by other sources, such as a recent Canadian dictionary and a corpus of Canadian English. Our methodology allows us to observe French loanwords and their patterns of evolution from a semantic point of view. More traditional treatments of loanwords in terms of zero semantic extension, restriction or expansion of meaning (Filipovic 1968) soon find their limits and fail to offer a more comprehensive treatment of semantic change for the whole lexicon, since both the native lexicon and borrowings seem to follow similar paths in their semantic evolutions. The mechanisms of narrowing and broadening of meaning operating in lexical pragmatics for the native lexicon are the same as for loanwords once they have been integrated in the recipient language. While giving more importance to context and allowing a more unified lexical treatment, this approach raises several questions as far as the basic assumption of a linguistically-specified meaning is concerned. Consequently, we propose to adopt another perspective, a usage-based approach, which stresses the central role played by context and usage in the understanding of semantic change, particularly in a diachronic perspective. Our methodology is compatible with that type of approach. By positing the existence of exemplars which are stored in the mental lexicon with all their features, including meanings and inferences in context, we assume that meaning is not necessarily encoded linguistically and therefore fixed but that it can be stored and become conventionalized through use. This approach also allows us to explain cases of metonymy or metaphor we encountered and which can sometimes be challenging to tackle in other theoretical frameworks.